Long-term multimodal imaging characterization of persistent retinal neovascularization using DL-alpha-aminoadipic acid in pigmented and white rabbits. (June 2021) - Yu, Yixin; Qin, Yu; Fu, Julia; Li, Yanxiu; Zhang, Wei; Zhu, Tianye; Jiang, Longtan; Wang, Xueding; Paulus, Yannis M.
Abstract: Purpose: Intravitreal (IVT) injection of DL-alpha-aminoadipic acid (AAA) is a new animal model for retinal neovascularization (RNV) reported in rabbits. This study performs longitudinal multimodal imaging for up to 1 year to evaluate DL-AAA RNV in both New Zealand white (NZW) rabbits and Dutch-Belted pigmented (DBP) rabbits. Method: Detailed characterization and quantification of this model were performed in these two strains in 32 eyes by optical coherence tomography (OCT), fundus photography, and fluorescein angiography (FA) for up to 16 weeks following DL-AAA administration in 32 eyes and up to 52 weeks in 5 eyes. H & E histology was also performed in these two strains 8 weeks after injection of DL-AAA. Result: RNV was successfully generated using 50 μL 80 mM DL-AAA solution for DBP rabbits and 80 μL 80 mM DL-AAA for NZW rabbits. The incidence of persistent vascular leakage is 100% (15/15) for DBP rabbits and 70.6% (12/17) for NZW rabbits at 16 weeks. Complications with NZW rabbits ultimately decreased the efficiency in NZW rabbits to 58.8% (10/17) of NZW rabbits getting persistent (to 16 weeks) vascular leakage without ocular complications as compared with 100% (15/15) in DBP rabbits. Five eyes (2 DBP and 3 NZW) were selected from those demonstrating RNV at 16 weeks and were monitored for up to 52 weeks. All 5 demonstrated persistent RNV to 52 weeks. Quantification of the mean leakage area (MLA) in DBP rabbits is more accurate than in NZW rabbits since the reduced contrast between the leakage and background in NZW rabbits makes it more challenging to quantify. Conclusion: DL-AAA can induce persistent and quantifiable RNV in both DBP and NZW rabbits. DBP rabbits have a higher success rate, lower required volume of DL-AAA, and more accurate method for quantification that could be more desirable. Highlights: Intravitreal injection of DL-AAA is a novel animal model for chronic retinal neovascularization (RNV) for at least 1 year. DL-AAA induced persistent RNV in 100% (15/15) DBP rabbits and 70.6% (12/17) NZW rabbits at 16 weeks. NZW Rabbits had a higher rate of ocular complications, and were more challenging to quantify the area of leakage.